METAMORPHOSIS FROM MUSIC TO POLITICS: STUDY ON CELEBRITY GIRING GANESHA IN INDONESIAN LEGISLATIVE ELECTION - Achmad Jamil; Rizki Briandana; Rustono Farady Marta; Fahmi Fotaleno; Muhammad Raqib Mohd Sofian (Profetik: Jurnal Komunikasi, 2022)
This study aims to analyze the metamorphosis of Giring Nidji from Music Stage to Politics Stage. Political dynamics in Indonesia are an attraction for all groups and levels of society, including musicians. This research begins by looking at the phenomenon of artists who have entered the world of politics, in this case Giring Ganesha, the vocalist of the band Nidji. He decided to leave the world of music that had raised his name to advance in the 2019 Legislative Candidate Election. After 15 years of working in the music world with his band Nidji, Giring Ganesha finally decided to resign and chose to enter politics. This study used the Symbolic Interaction Theory of George Herbert Mead and Herbert Blumer. This type of research is qualitative with a constructivist paradigm using a case study research method. The data collection techniques used interviews and observations. Four informants were selected as the main data and Giring himself was the key informant in this study. The results of this study indicate that in the metamorphosis process of Giring Ganesha from a musician to a politician, he has gone through several long stages such as preparation stage, play stage, game stage, generalizing stage, and becoming a legislative candidate. Eventually, he has formed his current self-concept and thoughts as a politician.